Gastronomic Tourism as a Means of Activating Tourist Destinations - Maryna Rubish; Myroslava Choriy; Lilia Zelenska (Науковий вісник Мукачівського державного університету. Серія Економіка, 2020)
The relevance of the study lies in the impact of gastronomic tourism on the development of the tourism sector and the fact that gastronomic tourism is a means of activating tourist destinations; supporting national producers by integrating gastronomic tourism into local event resources. Given the lack of a holistic understanding of the concept of gastronomic tourism, the imperfection of existing recommendations and conclusions on its development, there is a need for a detailed analysis of the subject. The purpose of the paper is to study the features of gastronomic tourism as a means of activating the development of the tourism sector. The paper covers that gastronomic tourism is based on the specific features of regional cuisine and culinary traditions of the tourist destination. It was established that from the standpoint of organising tourist activities, gastronomic tourism includes not only familiarisation with the local cuisines of the region but also original technologies for organising local food, culinary processes and food traditions, local products, as well as the opportunity for tourists to take part in the preparation of national dishes, visiting culinary festivals, various types of tastings and competitions. The originality of the research results consists in deepening theoretical approaches to the study of gastronomic tourism – a new area of cultural and educational tourism, which is relevant to combine with eco-tourism, tourism in protected areas, rural green tourism. In particular, rural green tourism is rich in cultural, culinary, authentic traditions, and is valuable for revival and development